Clustering of major cardiovascular risk factors is associated with arterial stiffness in adults - Xiang-Lei Kong (KeAi Communications Co., Ltd., 2018)
Objective: Cardiovascular disease (CVD) is the leading cause of mortality and morbidity worldwide. Previous studies have indicated that clustering of major CVD risk factors is common. We aimed to explore the association of clustering of CVD risk factors with arterial stiffness in adults. Methods: A total of 9984 adults were enrolled. We investigated clustering of four major CVD risk factors (defined as two or more of the following: hypertension, diabetes, dyslipidemia, and high body mass index) and their association with arterial stiffness. Arterial stiffness was evaluated using the carotid-femoral pulse wave velocity (cfPWV). Results: In the study group (52.2% men, the mean age was 55.4 ± 10.5 years; only 11.9% of participants were free of any pre-defined CVD risk factors and 61.8% of participants had clustering of CVD risk factors. The cfPWV was significantly higher in the clustered risk factors group than in the no risk factor or the single risk factor groups (16.1 ± 3.1, 13.4 ± 2.2, and 14.3 ± 2.6 m/s, respectively; P < 0.001). Multiple linear regression analysis revealed that age, gender, clustering of CVD risk factors, serum uric acid, and decreased renal function positively correlated with cfPWV. For a categorical outcome, the highest cfPWV quartile (cfPWV ≥ 16.9 m/s) was compared with the lower three quartiles. After adjusting for potential confounders, clustering of CVD risk factors significantly correlated with increased cfPWV compared with that in the no risk factor group, with an odds ratio of 5.76 (95% confidence interval: 4.46–7.44). Conclusions: Clustering of CVD risk factors significantly correlated with arterial stiffness; this confirms the importance of lifestyle modification to reduce the burden of CVD. Keywords: Cardiovascular disease, Cluster, Arterial stiffness, Pulse wave velocity